MEDIASI DAN ADVOKASI PANDEMI COVID-19 PADA MASYARAKAT DESA GIRIMUKTI KECAMATAN SAGULING - Enjang Aris Somantri (Jurnal Al Maesarah, 2022)
Corona virus disease (covid-19) which started in Wuhan, China and then spread all over the world, have a broad impact. Public perception of Covid-19 is very diverse which has the potential to change aqidah. Therefore, it is necessary to provide assistance to people that affected by COVID-19. The Community Service Program is one of the tridharma obligations of higher education that must be implemented. This community service program was carried out in Girimukti Village, Saguling District, West Bandung Regency. This program is intended to provide counseling and assistance to the society regarding perceptions about the COVID-19 pandemic. The method used in this service is a mediation and advocacy method, where the community is given mediation of understanding about covid-19 and given advocacy to the community regarding the covid-19 vaccine. The results shown through this community service program are very good. The community can understand that this pandemic is one of the destiny of Allah and as a form of grateful to Allah for His gift of health. People began to understand the importance of vaccines and participated in vaccine programs that organized by the government.